Religion as a social determinant of health in old age? - Idler, Ellen (Journal of religion, spirituality & aging, 2024)
This paper will argue that religion has a special meaning for older adults beyond the findings in the research literature on religion’s effects on health outcomes. Research on religious involvement and health from the past several decades shows a strongly beneficial relationship for persons of all ages, and one that is heightened in old age. Given the pace of secularization, however, the future is uncertain and coming cohorts of older persons may not have the same life course experiences to draw on in late life.